Divergent Syntheses of Carbazole Alkaloids - Ji, Feixiang; Huang, He; Li, Mengyang; Guo, Yanqin; Song, Chuanjun; Chang, Junbiao (Synthesis, 2018)
Starting from common intermediate methyl 1-hydroxy-9H-carbazole-3-carboxylate, synthetic routes toward murrayaquinone A, olivacine, and N-methylcalothrixin B were developed.
Keywords: carbazole alkaloids; murrayaquinone A; olivacine; N-methylcalothrixin B; total synthesis